A Note About the Definition of Response Propensity for Survey Nonresponse. (1st May 2021) - Little, Roderick J
Abstract: Nonresponse propensities play a central role in unit nonresponse adjustments from both design and model-based perspectives, but are often not clearly defined because of lack of clarity about the variables on which the propensities are conditioned. A definition of response propensity for the purpose of nonresponse adjustments is proposed, where the conditioning is restricted to include the variables measured in the survey as well as design and auxiliary variables measured for respondents and nonrespondents. The proposed definition is justified from both design-based and model-based perspectives. The role of the missing at random assumption is discussed for both perspectives, for cross-sectional surveys and longitudinal surveys with attrition.